2008
DOI: 10.1007/s10530-008-9274-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in the grazing potential of the invasive amphipod Gammarus tigrinus and the native amphipod Gammarus salinus (Amphipoda: Crustacea) in the northern Baltic Sea

Abstract: Mesograzers are known to reduce the biomass of their host plant and modify the structure of the whole macrophyte community in many ecosystems. Thus, the introduction of an efficient mesograzer may destabilize macrophyte community and also affect the native grazers. We estimated how large proportion of macrophyte production are consumed by the alien gammarid G. tigrinus and the native gammarid G. salinus in the species poor ecosystem of the northern Baltic Sea. We analysed whether G. tigrinus consumes different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…Previous studies from the Netherlands (Pinkster et al 1977) and Northern Ireland (Dick 1996) highlighted the predation of invertebrates and fish eggs by this invasive species. However, some experimental studies have shown that G. tigrinus also consumes different types of algae (Orav-Kotta et al 2009) and Rong et al (1995) observed the consumption of leaf litter. Due to the differential leaf litter breakdown rates between native and invasive species and the decrease in amphipod biomass, the replacement of native species by invaders should lead to a strong decrease in leaf litter recycling in rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from the Netherlands (Pinkster et al 1977) and Northern Ireland (Dick 1996) highlighted the predation of invertebrates and fish eggs by this invasive species. However, some experimental studies have shown that G. tigrinus also consumes different types of algae (Orav-Kotta et al 2009) and Rong et al (1995) observed the consumption of leaf litter. Due to the differential leaf litter breakdown rates between native and invasive species and the decrease in amphipod biomass, the replacement of native species by invaders should lead to a strong decrease in leaf litter recycling in rivers.…”
Section: Discussionmentioning
confidence: 99%
“…However, its effective spread and dominance may also be due to earlier maturation and greater brood size (both traits were indicated in these experiments), faster juvenile growth, longer and more frequent reproductive periods, higher reproduction rates and greater longevity. Additionally, G. tigrinus predates on indigenous species (Grabowski et al 2007b) as well as other non-indigenous species (Platvoet et al 2009) and it is also said to be a strong competitor for food and habitat (Orav-Kotta et al 2009). All these traits may further contribute to its dominance and success.…”
Section: Discussionmentioning
confidence: 99%
“…Non-linear responses are common in experiments testing pharmaceuticals and other emerging substances (e.g. Calabrese & Baldwin 2001, De Lange et al 2006, 2009, Eriksson Wiklund et al 2012 in press). Although the measured effect concentrations are higher than environmental concentrations, the traditional predicted environmental concentrations (PEC) to predicted no-effect concentration (PNEC) ratio approach in risk assessment would indicate a high relevance to the environment (Cleuvers 2005).…”
Section: General Implicationsmentioning
confidence: 99%
“…and macroalgae like F. vesiculosus are interdependent and constitute an important key community of the Baltic Sea (Råberg & Kautsky 2007). By feeding on the macroalgae, the amphipods both degrade the macroalgae itself and remove impeding epibiota (Orav-Kotta et al 2009). Consequently, the amphipods affect the macroalgal structure and productivity (Arrontes 1999) and constitute an important link in the littoral community, connecting primary producers to secondary consumers in the coastal zone (MacNeil et al 1999).…”
Section: Introductionmentioning
confidence: 99%